Introduction to compressible fluid flow - Oosthuizen, P. H.; Carscallen, William E. (CRC Press, 2014)
"Highlighting aspects of compressible fluid dynamics often missed in undergraduate courses, this text reviews background material and lays the foundation for more advanced and specialized courses such as Hypersonic Flow and Low Density Flows. With a wealth of updated and expanded material, this second edition includes numerical results obtained using a modern commercial computer fluid dynamics code, focuses on supporting software and practical applications, provides additional numerical and non-numerical problems, replaces BASIC with MATLAB® routines, and offers COMPROPS 2 software for compressible flow computation"--Vydavatelská anotace
Keywords: dynamika tekutin; proudění tekutin; počítačová mechanika tekutin; fluid dynamics; fluid flow; computational fluid dynamics; monografie; monographs